Análisis del ancho de calles de las manzanas urbanas en el Área metropolitana de Mendoza, Argentina - Arboit, Mariela Edith (UNIVERSIDAD DE SONORA, 2022)
The study analyzes the width of streets in the Mendoza Metropolitan Area (AMM) and its six departments, as part of the problem of environmentally and energetically sustainable development of the building sector in cities of the arid region of central-western Argentina. The urban-building morphology is closely related to the energy conditions and urban comfort, so the knowledge of the characteristics of the urban layout and the availability of data to evaluate the possibilities of implementing strategies in densification, renovation, rehabilitation and Urban zone design is very useful for more energy efficient planning in cities with population growth and urban expansion. Methodologically, the urban variable street width was quantified and urban blocks were categorized according to said variable for the AMM in geographic information systems (GIS). The results for the urban blocks were statistically analyzed and density graphs were constructed from the defined categories. The evaluation indicates an average street width value of 19.07m. The conclusions of the spatial study show that it is possible to develop energy strategies based on existing street widths, identifying priorities by departments.